TRANSFORMASI KEKERABATAN DI ERA DIGITAL: ANALISIS INTERAKSI SIMBOLIK DALAM KOMUNIKASI KELUARGA - Nursida, Andi; Fatmawati, Fatmawati; Ismail, Lukman; Maemunah, Maemunah; Mukramin, Sam'un (Institut Agama Islam Ngawi, 2025)
The development of digital technology has brought significant changes in social interaction patterns, especially in kinship relationships. This study aims to understand how kinship dynamics change in the digital era using the symbolic interaction perspective introduced by Herbert Blumer. This study uses a qualitative approach with a document study method to analyze various secondary sources related to changes in social interaction in families. The results of the study indicate that the use of social media and communication technology has changed the form of family communication from face-to-face to digital-based. This allows geographically separated families to stay connected, but also presents challenges in maintaining emotional closeness. The use of digital symbols such as emojis, stickers, and video calls replaces physical expressions in communication, which can affect the depth of social interaction in kinship relationships. This study also found that shifts in communication patterns in families can affect solidarity and social support between family members. Digital technology can be a means to strengthen or weaken kinship relationships depending on how individuals interpret it in their daily lives. Thus, this study provides important insights for academics and social practitioners regarding the impact of technology on social interaction and family dynamics in the digital era. Keywords: Symbolic interaction, kinship, digital technology, social media, family communication